High‐Speed Coating of Primer Layer for Li‐Ion Battery Electrodes by Using Slot‐Die Coating. Issue 9 (16th July 2020) - Diehm, Ralf; Müller, Marcus; Burger, David; Kumberg, Jana; Spiegel, Sandro; Bauer, Werner; Scharfer, Philip; Schabel, Wilhelm
Abstract : A reduction of the inactive components can increase the energy density and reduce production cost of Li‐ion batteries. But an effective reduction of the binder amount also negatively affects the adhesion of the electrode. Herein, slot‐die coating of a primer layer for Li‐ion anodes is investigated. It is shown that the use of a primer layer with only 0.3 g m −2 can increase the adhesive force by the factor of 5 as well as the cell performance for anodes with low binder content. The process limits for a stable, defect‐free primer coating are investigated at coating speeds of up to 550 m min −1 . The limits coincide both for a setup without vacuum box and with vacuum box with theory‐based equations. By using a vacuum box, the minimum wet film thickness can be reduced by half. Abstract : The use of primer layers is a promising way to improve the properties of lithium‐ion battery electrodes. This study considers the process window for industrial‐related slot‐die coating of primer at very high coating speeds. A vacuum‐stabilized coating bead enables cost‐effective production of very thin wet film thicknesses at coating speeds of over 550 m min −1 .